Applying Bipartite Network Approach to Scarce Data: Validation of the Habitat Suitability Model of a Marine Mammal Species - Liew, ChinYing; Labadin, Jane (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper presents the validation of the bipartite habitat suitability network (BiHSN) model formulated for a marine mammal. The model formulation published earlier resulted in the ranking of location nodes of the concerned area of possible habitats. Thus, the validation of the model is achieved by comparing the result produced by the BiHSN Model with the result acquired i) using another sample of actual data; and ii) from an ecological survey conducted by another researcher. Spearman’s Rank Correlation Coefficient (SRCC) is used to quantify the similarity of the comparison where a threshold value of at least 0.70 is set in order to signify an acceptable validation analysis. In the former validation analysis, this study reports an SRCC of 0.976 whereas the later validation analysis reports an SRCC of 0.914. Due to the high values of SRCC obtained, we conclude that the BiHSN Model is thus validated.